Pola Komunikasi Interpersonal Santri dalam Menjaga Solidaritas di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo - Durrotin Nafisah; Yohandi Yohandi; Nur Ainiyah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2021)
The success of communication activities is highly dependent on the communication skills of the communicator. This article will discuss how the interpersonal communication patterns of female students in maintaining solidarity at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo. The method used is a qualitative method with the intention of describing the behavior of informants, namely the interpersonal communication pattern of the Room Residents to maintain solidarity at the Salafiyah Syafi'iyah Islamic Boarding School. The results show that the communication pattern applied in maintaining the solidarity of female students is using interpersonal communication which is divided into two types, namely dyadic communication (interpersonal communication) and small group communication. The good relationship between female students and the role of the head of the room is very decisive while maintaining the solidarity that has been created, so that there is mutual trust, because when mutual trust arises, they respect each other